Intracranial hypertension after doxycycline sclerotherapy of a large macrocystic lymphatic malformation in an infant - Angela C. Lee; Ranjith Vellody; Richard Kaplan; Bhupender Yadav (Elsevier, 2021)
We present a case of an infant who developed intracranial hypertension after Doxycycline sclerotherapy of a large right axillary macrocystic lymphatic malformation secondary to significant absorption of the drug. This case highlights the association between Doxycycline and intracranial hypertension, even when it is used as a sclerosing agent. Clinicians performing and taking care of infants post sclerotherapy need to be aware of this potential association so any signs of intracranial hypertension post sclerotherapy can be identified and treated accordingly.